2003
DOI: 10.1093/genetics/165.4.2071
|View full text |Cite
|
Sign up to set email alerts
|

Sequences Associated With Human Iris Pigmentation

Abstract: To determine whether and how common polymorphisms are associated with natural distributions of iris colors, we surveyed 851 individuals of mainly European descent at 335 SNP loci in 13 pigmentation genes and 419 other SNPs distributed throughout the genome and known or thought to be informative for certain elements of population structure. We identified numerous SNPs, haplotypes, and diplotypes (diploid pairs of haplotypes) within the OCA2, MYO5A, TYRP1, AIM, DCT, and TYR genes and the CYP1A2-15q22-ter, CYP1B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(19 citation statements)
references
References 50 publications
1
15
0
3
Order By: Relevance
“…A recent whole genome scan indicated that more than 70% of eye colour variation is due to QTL localised on chromosome 15q [1]. This observation is in good concordance with some other results suggesting that the OCA2 gene located in this area may be involved in normal variation in eye colour among humans [2,3]. The OCA2 gene consists of 24 exons spanning a region of 345 kb and encodes an 838 amino acid protein (P), which contains 12 transmembrane domains.…”
Section: Introductionsupporting
confidence: 62%
“…A recent whole genome scan indicated that more than 70% of eye colour variation is due to QTL localised on chromosome 15q [1]. This observation is in good concordance with some other results suggesting that the OCA2 gene located in this area may be involved in normal variation in eye colour among humans [2,3]. The OCA2 gene consists of 24 exons spanning a region of 345 kb and encodes an 838 amino acid protein (P), which contains 12 transmembrane domains.…”
Section: Introductionsupporting
confidence: 62%
“…We extracted DNA using Proteinase K (Promega, USA) and LiCl (Gemmell & Akiyama, 1996), and quantified it by using the Nanodrop spectrophotometer (Thermofisher). Then, we genotyped the samples for the six SNPs of the IrisPlex: rs12913832:A>G, rs1800407:C>T, rs12896399:G>T, rs16891982:C>G, rs1393350:G>A, and rs12203592:C>T, and additionally, another four SNPs: rs1129038:C>T, rs7183877:C>A, rs1800410:G>A and rs4778232:T>C. These polymorphisms are located in genes associated with eye color ( HERC2, OCA2, LOC105370627, SLC45A2, TYR , and IRF4 ) (Duffy et al., 2007; Eiberg et al., 2008; Eriksson et al., 2010; Frudakis et al., 2003; Han et al., 2008; Lippert et al., 2017; Liu et al., 2009; Palmal et al., 2021; Ruiz et al., 2013; Visser et al., 2012; Wollstein et al., 2017). We designed oligonucleotides with Primer‐BLAST (Ye et al., 2012) and performed polymerase chain reaction (PCR) using recombinant Taq polymerase (T‐Plus, Inbio‐Highway, Tandil, Argentina), as well as the thermocyclers MPI (La Plata, Argentina) and Biometra T3000 (Biosciences, Dublin, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…However, the bulk of available studies on EVC genetics is mainly focused on European populations (Liu et al., 2009; Mengel‐From et al., 2009; Shapturenko et al., 2019; Sulem et al., 2007; Walsh et al., 2012), and only more recently, the scientific community began to analyze this topic in admixed populations (Beleza et al., 2013; Edwards et al., 2015; Lloyd‐Jones et al., 2017), especially from Latin America (Carratto et al., 2019, 2020, 2021; Hohl et al., 2018; Marano et al., 2019; Palmal et al., 2021; Silva de Cerqueira et al., 2014). Considering that differences in the genetic pool of a population can influence phenotype predictions based on genotype information (Beleza et al., 2013; Carratto et al., 2019, 2020, 2021; Frudakis et al., 2003; Popejoy & Fullerton, 2016; Sirugo et al., 2019), there is a need for these comprehensive studies in admixed populations.…”
Section: Introductionmentioning
confidence: 99%
“…The region on chromosome 15, including the OCA2 gene, was implicated in eye colour via linkage and subsequent fine-mapping analyses [ 12 , 13 ]. The evidence of a relationship between OCA2 genotypes and eye colour became stronger with additional reports [ 14 , 15 , 16 ]. This was an Icelandic GWAS that implicated the involvement of neighbouring HERC2 in the determination of eye colour and suggested that this genomic region was responsible for the regulation of OCA2 gene expression [ 17 ].…”
Section: Explaining the Heritability Of Appearance Traitsmentioning
confidence: 86%
“…The practical importance of a simple amelogenin genetic sex test [ 94 ], and also of the inference of biogeographical ancestry [ 95 , 96 ], made it clear that a description of the phenotypic characteristics of a person of undetermined identity can provide important investigative leads. The variation of the MC1R gene was soon proposed as an indicator of red hair colour [ 97 ], while the predictive potential of the OCA2 variation was proposed for the inference of eye colour [ 14 ]. The availability of GWAS data has made it possible to develop tools for predicting human appearance traits more effectively.…”
Section: Dna-based Predictive Tools For Forensic Applicationsmentioning
confidence: 99%